If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7 = 3(2x + -3) Reorder the terms: -7 + 4x = 3(2x + -3) Reorder the terms: -7 + 4x = 3(-3 + 2x) -7 + 4x = (-3 * 3 + 2x * 3) -7 + 4x = (-9 + 6x) Solving -7 + 4x = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7 + 4x + -6x = -9 + 6x + -6x Combine like terms: 4x + -6x = -2x -7 + -2x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 -7 + -2x = -9 + 0 -7 + -2x = -9 Add '7' to each side of the equation. -7 + 7 + -2x = -9 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = -9 + 7 -2x = -9 + 7 Combine like terms: -9 + 7 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| y^2=2 | | 2(4x+3)-4=3x+11+2x | | x+4+X-1= | | y^2+4y+3=0 | | 7a+4(a+3)=33 | | -3b+14=-4 | | x+20=3x+6 | | 5t^2-7t=60 | | x=2,5/10 | | 1x=1/1 | | 4(2x-1)+8=2x | | (c+o+l+l+e+e+n)*(c+o+l+l+e+e+n)=x | | 5+3G=3+5 | | x+q=q^5+13840934 | | X^4-9X^2-81=0 | | 5x=240 | | -2(2+-2b)+b=8 | | 5h-2=10 | | 4(5x-8)=88 | | -6x-3.4=3x+2.0 | | 6xy(3x^2-4y^2)= | | 4x+3.0=-4x-2.6 | | 4(2s)-3s=15 | | 5x=260 | | -4+-1t-t=2 | | -3s+4s=10 | | r=-3s | | 4p^2-29-20=0 | | 11m=44 | | 7x-2+4=10+5x | | 3x+3+9x-1=6x+12+2x | | (2p+3)(2p-4)=8 |